In Vivo Noncontact Imaging of Conjunctival Goblet Cells with Customized Widefield Fluorescence Microscopy - Yushuang Liu, MS; Zhengyu Duan, PhD; Zhongzhou Luo, BEng; Runze Zhang, MS; Jiaxiong Li, MS; Jinze Zhang, PhD; Zeyu Meng, MS; Bowen Wang, MD, PhD; Jin Yuan, MD, PhD; Peng Xiao, PhD (Ophthalmology Science)
Purpose: Conjunctival goblet cells (CGCs) play a crucial role in maintaining ocular surface health by producing mucins. However, assessing CGC changes in ocular diseases remains limited by invasive techniques and subjective evaluations. This study aims to develop a noncontact cellular resolution fluorescence microscopy for in vivo CGC imaging and investigate CGC dynamics in a dry eye disease (DED) mouse model. Design: Experimental study. Subjects: Freshly ex vivo porcine eyes, New Zealand white rabbits, and C57BL/6 mice. Methods: Based on the intrinsic fluorescence properties of moxifloxacin, a high-resolution noncontact widefield fluorescence microscopy (WFFM) was customized with an all-in-focus algorithm to optimize in vivo CGC imaging over the curved conjunctival surface. A DED mouse model was established by topically applying 0.2% benzalkonium chloride (BAC) to the ocular surface daily for 7 days, followed by a 7-day recovery period without BAC. In vivo CGC alterations were assessed using WFFM on days 0, 3, 7, and 14. Additional assessments included the phenol red thread tear test, corneal sodium fluorescein staining, and periodic acid–Schiff (PAS) assay. Main Outcome Measures: Conjunctival goblet cell density and area ratio. Results: The WFFM system achieved a cellular resolution of 1 μm and a field of view of 1.4 mm × 1.4 mm. Imaging validation in mice and rabbits allowed for the distinguishing and quantitative assessment of individual CGCs or clusters on the curved conjunctival surface in vivo. Significant reductions in CGC density and area ratio on days 3 and 7 after BAC induction were observed in DED mouse in vivo with WFFM, with their values returning to the baseline 7 days after BAC removal, which was consistent with PAS staining results. Conclusions: The customized WFFM enables in vivo cellular imaging of CGCs, offering a safe and accurate method for continuous monitoring of CGC pathophysiology in ocular surface diseases such as DED. Financial Disclosures: Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.